A Panda fiber temperature sensor up to 900°C. (1st July 2022) - Hokkanen, A.; Salmi, A.; Vashistha, V.; Nyman, M; Nielsen, S.K.; Jensen, T.; Jessen, M.; Wälchli, B.; Kapulainen, M.; Naulin, V.; Tala, T.; Aalto, T.
Abstract: The use of Panda-type polarization-maintaining (PM) fiber for the localized sensing of high temperatures was analyzed with simulations and experiments up to 900°C. Accuracy and repeatability of the results started to decline above 800°C. Fused silica optical fiber melts at 1700°C, which sets an ultimate limit for measurable temperatures. In practice, optical fiber birefringence restricts the maximum temperature to 1060°C where PM fiber loses its ability to maintain polarization. Three sensor fibers (4, 5 and 10 cm long) were spliced at 45° angles to input/output fibers and calibrated in an oven from room temperature to 850–900°C temperature range. Two superluminescent light-emitting diodes (SLEDs) were coupled together as a broadband light source. Birefringence-induced change of the polarization in the sensor fiber was measured with a polarization splitter and an optical spectrum analyzer (OSA) as a function of the wavelength. Temperature-dependent birefringence generates a sinusoidal reflection spectrum from the input polarization mode to the orthogonal output polarization mode. Temperature changes could be concluded from variations in these spectra. Finally, a small fusion device, NORTH, at DTU, Denmark was successfully used as a testbed to make sure that the sensors can handle transportation and the instrumentation required for vacuum operation and still produce sensible data from a harsh environment.